COVID-19 disease emergency operational instructions for Mental Health Departments issued by the Italian Society of Epidemiological Psychiatry. (31st March 2020) - Starace, Fabrizio; Ferrara, Maria
Abstract: During the current COVID-19 disease emergency, it is not only an ethical imperative but also a public health responsibility to keep the network of community psychiatry services operational, particularly for the most vulnerable subjects (those with mental illness, disability, and chronic conditions). At the same time, it is necessary to reduce the spread of the COVID-19 disease within the outpatient and inpatient services affiliated with Mental Health Departments. These instructions, first published online on 16 March 2020 in their original Italian version, provide a detailed description of actions, proposed by the Italian Society of Epidemiological Psychiatry, addressed to Italian Mental Health Departments during the current COVID-19 pandemic. The overall goal of the operational instructions is to guarantee, during the current health emergency, the provision of the best health care possible, taking into account both public health necessities and the safety of procedures. These instructions could represent a useful resource to mental health providers, and stakeholders to face the current pandemic for which most of Mental Health Departments worldwide are not prepared to. These instructions could provide guidance and offer practical tools which can enable professionals and decision makers to foresee challenges, like those already experienced in Italy, which in part can be avoided or minimised if timely planned. These strategies can be shared and adopted, with the appropriate adjustments, by Mental Health Departments in other countries.